PENERAPAN MODUL PENILAIAN MISKONSEPSI IPA MATERI SUHU DAN KALOR TERINTEGRASI CRI (Certainly Of Response Index) MELALUI METODE BLENDED LEARNING - Yaspin Yolanda (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2021)
A B S T R A C TThis study was taken based on the results of observations and interviews of researchers at SMP Negeri 2 Lubuklinggau which showed that many students had misconceptions in science about temperature and heat, as many as 84 percent of students had misconceptions about the concept of changing temperature from Celsius to Fahrenheit, 75% of students did not understand the meaning of temperature and heat material In everyday life, students' misconceptions about changes in the state of matter and factors of heat change. This study aims (1) how to analyze students' misconceptions on temperature and heat material after applying the Blended Learning model and (2) measure the validity and practicality of the temperature and heat science misconception assessment module according to students' needs. The location of this research is SMP Negeri 2 Lubuklinggau City. This research was conducted in Class VII.1 and VII.2 even semesters, namely from January to July 2021. The development model used was the Borg and Gall models. Data collection techniques in this study 1) documentation based on the CRI Diagnostic Test, 2) interviews, and 3) questionnaires. Analysis of the data that has been collected was analyzed by quantitative descriptive. Based on the results of research using the temperature and heat science misconceptions assessment module, the validity level is 37.5% (valid), the average field test student response is 3.8 with a very practical category and the effectiveness of the science misconception assessment module increases the number of students who understand the concept of using the Blended Learning model of 95.03% (very good). The effectiveness of the module is seen from the student's test scores after using the Science misconceptions assessment module for Temperature and Heat material. There are 80 students who take the test. There are 12 students who understand the concept and 68 students still have misconceptions.